(3eNGQL GdMQhas - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3fhM Hf jhSa Ydi GdShQGJi s)
(3ChdgG (B:s
(3GdMeO ddg hMOg MeOkG jSJGgdg HYXeI PGJg hHYO adjS cd bGHd gOjI eMJGLkG GdjgG hdG cd WGdH JMaI aGbOkG dgG s
(3BNQgG (B:s
(3hJSeY GcKQgG ef GdWjQ ef dZGJ Cee THjgI GddZGJ HfZe GdWjQ hGXf Efi bO HdZJ GdcaGjI hYHQJ Yf GdebOGQ GdPi jHdZg eYQaJi s
(3fbd GdfGSN GdaUd GdQGHY hGdSGOS ef fSNI CNQi eNGdaI deG ai gPg GdfSNI HYO GfJgGA GdfU (B}s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs